Associations of erythrocyte omega‐3 fatty acids with cognition, brain imaging and biomarkers in the Alzheimer's Disease Neuroimaging Initiative. (20th December 2022) - Rouch, Laure; Giudici, Kelly V; Cantet, Christelle; Guyonnet, Sophie; Delrieu, Julien; Legrand, Philippe; Catheline, Daniel; Andrieu, Sandrine; Weiner, Michael W.; Barreto, Philipe de Souto; Vellas, Bruno; ,
Abstract: Background: The association between ω‐3 polyunsaturated fatty acids and cognition, brain imaging and biomarkers is still not fully established. We aimed to analyze the cross‐sectional and retrospective longitudinal associations between erythrocyte ω‐3 index and cognition, brain imaging and biomarkers among older adults. Method: 832 participants from the Alzheimer's Disease Neuroimaging Initiative 3, mean (SD) age 74.0 (7.9) years, 50.8% female, 55.9% cognitively normal, 32.7% with mild cognitive impairment and 11.4% with Alzheimer's disease (AD) were included. Low ω‐3 index (% eicosapentaenoic acid EPA + % docosahexaenoic acid DHA) was defined as the lowest quartile (≤3.70%). Cognitive tests (composite score; AD Assessment Scale cognitive (ADAS‐Cog) subscale; Wechsler Memory Scale (WMS); Trail Making Test A and B; Category fluency; Mini Mental State Examination; Montreal Cognitive Assessment; Clinical Dementia Rating) and brain variables (hippocampal volume, white matter hyperintensities (WMH), PET amyloid‐β and Tau) were considered as outcomes in regression models. Result: Low ω‐3 index was not associated with cognition, hippocampal and WMH volume, brain Aβ and Tau after adjustment for age, education, ApoE ε4, cardiovascular disease, BMI and total intracranial volume in the cross‐sectional analysis. In the retrospective analysis, low ω‐3 index was associated with greater Aβ accumulation over time. The composite cognitive score did not differ between groups; however, low ω‐3 index was associated with greater cognitive decline on the WMS‐Delayed recall but unexpectedly lower cognitive decline on the total ADAS‐Cog. Low ω‐3 index was cross‐sectionally associated with lower performance on WMS tests and higher Tau accumulation among ApoE ε4 carriers. Conclusion: Longitudinally, low ω‐3 index was associated with greater Aβ accumulation over time and cognitive decline on the WMS but unexpectedly with lower cognitive decline on the total ADAS‐Cog. Low ω‐3 index was associated with lower cognition on the WMS and higher Tau accumulation among ApoE ε4 carriers in the cross‐sectional analysis.